PMO Typologies and Functions: A Systematic Review - El Yacoubi Zouheir; Jahidi Rachid (European Scientific Journal, ESJ, 2020)
In order to contribute to the development of knowledge about PMO, a systematic review has been conducted using several search engines. Based on specific criterion, several articles were selected for analysis. The thematic analysis method has been used to analyze and synthesize all the data collected. The results of this study have allowed to draw a time line evolution of PMO along with the main periods that characterize it. Moreover, it showed the existence of multiple forms of PMO that could be implemented by organizations and that can be associated to specific functions. It is a clear indication of the existence of diversified opinions about PMO in terms of typologies and functions. Each organization must focus much more on determining the role that the PMO will play and try to adapt its functions and responsibilities to fulfill its needs and be able to ensure positive impact. Simply put, in order to participate in performance improvement, the PMO implementation must be done with a perfect consideration of the organization characteristics.